2016
DOI: 10.1038/srep32953
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo shoot fiber prevents obesity in mice by modulating the gut microbiota

Abstract: Dietary fiber has been shown to prevent high-fat diet induced obesity through modulating the gut microbiota; however, quality difference in fiber type is largely unknown. We performed a 6 week study on C57BL/6J mice fed a macronutrient matched high-fat diet with different fiber types including cellulose (HFC), bamboo shoot fiber (HFBS) and several other commonly consumed fibers. Our results showed that the HFBS group exhibited the lowest weight gain among all diet groups and had improved lipid profiles and gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 55 publications
10
72
0
Order By: Relevance
“…In addition, dietary fiber also causes metabolic effects by decreasing fat storage because of increased satiety [9]. Similar results are reported when bamboo shoot fiber is used in mice test [12].…”
Section: Effects Of High-polydextrose Snack On Liver Functionsupporting
confidence: 71%
See 1 more Smart Citation
“…In addition, dietary fiber also causes metabolic effects by decreasing fat storage because of increased satiety [9]. Similar results are reported when bamboo shoot fiber is used in mice test [12].…”
Section: Effects Of High-polydextrose Snack On Liver Functionsupporting
confidence: 71%
“…Similarly, recent studies demonstrate that wheat fiber and phytochemicals isolated from wheat bran suppress body weight gain in high-fat dietfed mice [11]. In addition, bamboo shoot fiber also shows an effective role in suppressing high-fat diet-induced obesity than soluble fibers [12]. On the contrary, Weitkunat et al [13] reported that dietary fibers are discussed as factors influencing diet-induced obesity and energy homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…Akkermansia muciniphila is an intestinal mucindegrading bacterium (43). Li et al (44) reported that administration of bamboo shoots reduced the body weight gain and fat mass in high-fat-diet-fed mice. The relative abundance of Akkermansia was lower in the bamboo shoot-fed group.…”
Section: Discussionmentioning
confidence: 99%
“…55 For instance, bamboo shoot fiber was shown to prevent HFD-induced weight gain and insulin resistance in mice, and concurrently altered microbial composition including increased relative abundance of Bacteroidetes and decreased abundance of Firmicutes. 56 Inclusion of 10% (w/w) short chain FOS in HFDs (60% kcal from fat) altered microbial composition and function as measured by changes in metabolic byproducts of the microbiome. 57 In another report, maize-derived feruloylated oligo-and polysaccharides (FOPS) included at 5% (w/w) of a HFD (60% kcal from fat) improved outcomes in a subset of mice that correlated with changes in microbial structure.…”
Section: Prebioticsmentioning
confidence: 99%